Parametric Instability in Mathieu Equation in Earthquake Dynamics - Torres-Silva, H.; López-Bonilla, J.; Iturri-Hinojosa, A.; Torres Cabezas, D. (Himalayan Physics, 2017)
We propose an study of parametric resonance between P-waves and S-waves, which can be used to describe various nonlinear phenomena qualitatively and to obtain bifurcation diagrams quantitatively. We have shown that it is a good simulation of parametric phenomena, and our results are in good agreement with theoretical predictions. In particular, it may be used to study the influence of pump P waves on the instability’s threshold and amplitude of S waves in earthquake phenomena that could be simulated with an electronic model. The Himalayan Physics Vol. 6 & 7, April 2017 (73-75)